The Oxford handbook of governance and limited statehood - Risse, Thomas; Börzel, Tanja; Draude, Anke (Oxford University Press, 2018)
The Handbook gives a comprehensive picture of the varieties of governance in areas of limited statehood from interdisciplinary perspectives including political science, geography, history, law, and economics. 29 chapters review the academic scholarship and explore the conditions of effective and legitimate governance in areas of limited statehood, as well as its implications for world politics in the twenty-first century. The authors examine theoretical and methodological approaches as well as historical and spatial dimensions of areas of limited statehood, and deal with the various governors as well as their modes of governance. They cover a variety of issue areas and explore the implications for the international legal order, for normative theory, and for policies toward areas of limited statehood
Hier auch später erschienene, unveränderte Nachdrucke
Literaturangaben
Keywords: Aufsatzsammlung; Nachschlagewerk; Handbuch; Politisches System; Governance; Staatslehre; Internationale Politik; Nichtstaatlicher Akteur; Legitimität; Öffentliche Einrichtung; Begrenzte Staatlichkeit